New Directions in Hispanic Linguistics - Orozco, Rafael 1959- (Cambridge Scholars Publishing, 2014)
This volume addresses some lacunae in Hispanic linguistic research by focusing on new scholarly directions, exploring understudied topics as well as speech communities, and presenting new takes on relevant linguistic and sociocultural issues. This publication answers questions which have emerged as a result of the rapid increase in Hispanic linguistic research since the latter part of the twentieth century or that have remained open in spite of it. With the rapid growth of Hispanic Linguistics during the 21st century, the topics included in this volume are representative of the breadth, vitality, and interdisciplinarity of contemporary linguistic scholarship. They also reflect that linguistics, in general, has become more methodologically sophisticated. This book is comprised of twelve chapters divided into three parts. Part I addresses language ideology and language contact issues that are embedded in important sociolinguistic and cultural topics chronologically spanning from the 16th century to the present. Although these issues take place in Spain, the United States, Turkey and Ecuador, they pertain ideologically to all corners of the Hispanic World and beyond. Part II is devoted to pragmatics and language variation with topics that transport us to Colombia, Mexico, Spain and Venezuela. The study of politeness strategies shows how Spanish speakers reduce social distance between interlocutors as they make conversation a pleasant and cooperative meeting place. Concurrently, sociolinguistic innovations reveal interesting parallels among several speech communities. Part III explores linguistic variation as it relates to theoretical, structural, and instructional issues [...].
Description based on publisher supplied metadata and other sources
Keywords: Gesellschaft; Linguistik; Spanisch; Linguistics; Spanish language -- Social aspects; Spanish language; Hispanistik; Konferenzschrift -- 2012 -- Baton Rouge, La.